MY CART (5)

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price:

There are no items in this cart.
Continue Shopping
                   

If (1+ tan A)(1+ tan 4A)= 2, A E ( 0, π/16), THEN A is equal to


(a) π/20  (b) π/30   (c) π/40  (d) π/60


 Explain how???

3 years ago

Share

Answers : (2)

                                        

let A +B = pi/4 


tan(A+B)=1


or, tanA +tanB = 1-tanAtanB


or, (1+tanA)(1+tanB)=2




 use this result to obtain A+4A = pi/4


 


A= pi/20

3 years ago
                                        

(1+tanA)(1+tan4A)=2,


1+tanA+tan4A+tanAtan4A=2,


tanA+tan4A+tanAtan4A=1,


tanA+tan4A=1-tanAtan4A,


(tanA+tan4A)/(1-tanAtan4A)=1,


tan(A+4A)=tan45,


tan5A=tan45,


thus 5A=45,


A=9.


then (a) is the ans.

3 years ago

Post Your Answer

More Questions On Trigonometry

Ask Experts

Have any Question? Ask Experts
Post Question
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
what is the value of sin 4530
 
 
Here we get some rotations of 360 +330 extra left. 4530%360=330 the 220 left will be effective angle as argument.... sin 330=-sin(360-330)=-1/2;
 
Utkarsh Gupta one month ago
 
-1/2
 
srikanth one month ago
For all x in [ 0 , 90 ] show that cos ( s i n ( x ) ) > s i n ( c o s ( x ) ) I understood the solution given in my book which said cos ( x ) + sin ( x ) ≤ 2 √ 90 cos ( x ) 90 − sin ( x )...
 
 
Ans: Hello Student, Please find answer to your question below I am assuming 90 to be pi/2. For sinx will take value from 0 to 1 in increasing order. cosx will take value from 1 to 0. It is...
  img
Jitender Singh 8 months ago
if cosx+cosy+cosz=sinx+siny+sinz=0 then prove that sin2x+sin2y+sin2z=cos2x+cos2y+cos2z=0
 
 
hello student,, cosx + cosy = -cosz , cos^2x + cos^2y + 2cosx.cosy = cos^2z , in a similar way : sin^2x+sin^2y+2sinx.siny = sin^2z , add eqns & simplify : 1+1+2(cosx.cosy+sinx.siny) = 1...
  img
Nishant Vora 6 months ago
 
then what we have to do
 
Prashant Gulia 6 months ago
∫1/sqrt[a^3-x^3]
 
 
resolve into (a-x)(a^2+x^2+ax) ,then use partial fractions.
 
sarim khan 2 months ago
 
resolve into (a-x)(a^2+x^2+ax) ,then use partial fractions.
 
sarim khan 2 months ago
see attachment and explain it
 
 
Approach: we’ll first satisfy the condition given in the question. Answer: For filling each row with four letters taken at random, choices are 4. So in 4! ways. Now, we are free to...
  img
Ravi 5 months ago
View all Questions »